P018 AGE OF INITIAL COMPLAINT OF SEXUAL DYSFUNCTION AMONG INFLAMMATORY BOWEL DISEASE PATIENTS. (7th February 2019) - Khan, Ali; Dodds, Kerian L; Alabbas, Bedoor; Szvarca, Daniel; Clarke, Lindsay M; Tabbara, Nadeem; Borum, Marie L
Abstract: Background: There is a rise in incidence of Inflammatory Bowel Disease (IBD) among all age groups in the United States. IBD has many known extra-intestinal manifestations, however, there is limited data regarding its effects on sexual dysfunction. The aim of this study is to determine the prevalence of sexual dysfunction and the age of onset of sexual complaints among IBD patients. Methods: A retrospective chart review was performed of consecutive IBD patients seen during a five year period at an urban academic medical center. Patient gender, age, disease type, presence of sexual dysfunction, medications were obtained. The charts were evaluated for documented physician discussions about sexual dysfunction. A confidential database was created using Microsoft Excel with statistical analysis set at <0.05. There were no exclusion criteria. The study was approved by the IRB. Results: 261 IBD patients (121 males, 140 females; mean age 44.9) were evaluated. There were 76 patients (29.1%) with sexual dysfunction. 29 males (23.9%; mean age 43.2) and 47 females (33.6%; mean age 44.4) reported sexual dysfunction (p=0.042). The most common female sexual complaint was dyspareunia while that for males was erectile dysfunction. The average age of initial complaint among males was 47.2 and among females was 46.1. The frequency of complaints peaked in males who were 31-40 (24.1%) and peaked in females who were 31-40 (22.9%) and 51-60 (22.9%). (Figure 1).There was no significant difference (p=0.8) in the average age of initial complaint in Crohn's disease (which was 45.8) compared to ulcerative colitis (which was 47.9). (Figure 2). Discussion: In the general population, 7.4% males and 28% females are estimated to have sexual dysfunction. This study revealed that sexual dysfunction is significantly more prevalent among IBD patients than non-IBD patients. This was more prevalent in females and the age group of 31-40 years with no significant difference between those with Crohn's disease and ulcerative colitis. Although we recognize potential co-morbidities may be linked to sexual dysfunction, this study highlights the need for a consistent multidisciplinary approach to the IBD patient that addresses sexual function.